2022
DOI: 10.1080/15548732.2022.2044429
|View full text |Cite
|
Sign up to set email alerts
|

Differences in developmental problems between victims of different types of child maltreatment

Abstract: This study examined differences in developmental problems between children who were victims of two child maltreatment dimensions: abuse versus neglect, and physical versus emotional maltreatment. Family demographics and developmental problems were examined in a clinical sample of 146 Dutch children from families involved in a Multisystemic Therapy – Child Abuse and Neglect treatment trajectory. No differences were found in child behavior problems within the dimension abuse versus neglect. However, more externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
1
2
0
2
Order By: Relevance
“…Furthermore, the results demonstrated that resilience and self-esteem parallel mediated the relationships between CEM and aggression, suggesting that CEM not only has direct effects on aggression, but also has indirect effects though resilience and self-esteem. These results also suggested that resilience and self-esteem may play roles in the relationships between child maltreatment and later development, which has also been suggested by the results previous studies [ 6 , 38 ]. Moreover, Chinese people prefer constructing a self based on interpersonal relationships [ 62 ], which may contribute to severe impacts of CEM on resilience and self-esteem.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, the results demonstrated that resilience and self-esteem parallel mediated the relationships between CEM and aggression, suggesting that CEM not only has direct effects on aggression, but also has indirect effects though resilience and self-esteem. These results also suggested that resilience and self-esteem may play roles in the relationships between child maltreatment and later development, which has also been suggested by the results previous studies [ 6 , 38 ]. Moreover, Chinese people prefer constructing a self based on interpersonal relationships [ 62 ], which may contribute to severe impacts of CEM on resilience and self-esteem.…”
Section: Discussionsupporting
confidence: 86%
“…Aggression, as a method of externalizing problems, may be an index for later maladaptation, which may be influenced by adverse childhood experiences, such as childhood maltreatment [ 4 ]. Some studies have explored relationships between physical or sexual abuse and aggression [ 5 , 6 ] and relationships between CEM and aggression have also been confirmed by some studies [ 7 ], while the pathways from CEM to aggression remain unclear, particularly in the Chinese cultural context. Attachment theory posits that early interactions between a child and caregiver(s) may influence individuals’ internal working models about themselves, others, and interpersonal relationships, which may influence later development [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los análisis confirmaron la existencia de un número alto de estudios (80% de la muestra) que demuestran la co-ocurrencia de signos y síntomas entre los diferentes tipos de MI. Estos hallazgos son coherentes con los resultados de estudios previos realizados a nivel internacional (Bijlsma et al, 2022;Charak et al, 2018 2018) precisa que el indicador psicopatológico no debe ser considerado como un determinante de MI debido que existen diversos factores que pueden impedir el desarrollo de una patología. Lo expuesto, complejiza aún más la labor de los profesionales y ameritan evaluaciones integrales.…”
Section: Discusión Y Conclusiónunclassified
“…Los hallazgos corroboran que existen pocos estudios que emplean muestras con o sin MI para realizar análisis discriminantes con el criterio de grupos contrastantes (comparación intra e inter-grupos) (Matsumoto et al, 2021); análisis del efecto de la polivictimización (Bijlsma et al, 2022). De igual manera, se reconoce la persistencia de vacíos de conocimiento tales como: potencial de superposición, independencia entre los diversos tipos de MI, probabilidad de riesgo compartido, efectos de exposición prolongada, efectos de la exposición al trauma acumulativo (secuencial o simultaneo) (Bijlsma et al, 2022) y poco consenso para el establecimiento de indicadores de discriminación.…”
Section: Discusión Y Conclusiónunclassified